2015
DOI: 10.1073/pnas.1517810112
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Bmx tyrosine kinase activity is essential for myocardial hypertrophy and remodeling

Abstract: Cardiac hypertrophy accompanies many forms of heart disease, including ischemic disease, hypertension, heart failure, and valvular disease, and it is a strong predictor of increased cardiovascular morbidity and mortality. Deletion of bone marrow kinase in chromosome X (Bmx), an arterial nonreceptor tyrosine kinase, has been shown to inhibit cardiac hypertrophy in mice. This finding raised the possibility of therapeutic use of Bmx tyrosine kinase inhibitors, which we have addressed here by analyzing cardiac hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…ANG II induces ET-1 expression by activation of c-Jun/c-Fos (AP1) and formation of chromatin remodeling complex that includes AP1-mediated recruitment of a histone H3K4 trimethyltransferase, either SET1 or MRTF-A (1138,1139,1222). Others report that endothelial tyrosine kinase Bmx and subsequent activation of STAT3 is necessary for ANG II-induced cardiac hypertrophy and fibrosis due to the induction of proinflammatory cytokines (389). ANG II stimulates cardiac fibroblasts to produce FGF-2, which is important for concentric hypertrophy and preventing dilated cardiomyopathy (810).…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 99%
“…ANG II induces ET-1 expression by activation of c-Jun/c-Fos (AP1) and formation of chromatin remodeling complex that includes AP1-mediated recruitment of a histone H3K4 trimethyltransferase, either SET1 or MRTF-A (1138,1139,1222). Others report that endothelial tyrosine kinase Bmx and subsequent activation of STAT3 is necessary for ANG II-induced cardiac hypertrophy and fibrosis due to the induction of proinflammatory cytokines (389). ANG II stimulates cardiac fibroblasts to produce FGF-2, which is important for concentric hypertrophy and preventing dilated cardiomyopathy (810).…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 99%
“…Increased BMX expression was further confirmed by quantitative PCR (qPCR) analysis ( Figure 1B). BMX is a nonreceptor tyrosine kinase belonging to the Tec kinase family, which is highly expressed in myeloid and endothelial cells (11,12). BMX contains an SH2 domain that binds to tyrosine-phosphorylated proteins and a PH-like domain, which mediates membrane targeting by binding to phosphatidylinositol 3,4,5-triphosphate (PIP3) (13).…”
Section: Introductionmentioning
confidence: 99%
“…The Vegfr2 gene promoter activities were significantly lower in HUVECs with BMX siRNA than in HUVECs with Ctrl siRNA, as determined by the luciferase activity assay (Figure B). Several studies have found that BMX tyrosine kinase activity has diverse functions under different conditions . Next, we assessed whether BMX kinase activity was required for Vegfr2 promoter activation by rendering BMX catalytically inactive by mutating its ATP co‐ordination site (K445R; Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…In pathological cardiac hypertrophy development, inactivation of BMX abolished Ang II‐induced cardiac hypertrophy in mice. The effect of BMX on cardiac hypertrophy is mediated via the crosstalk between ECs of the coronary vasculature and cardiomyocytes . In another study, BMX kinase activity was found to be indispensable for IL‐8 promoter activation.…”
Section: Discussionmentioning
confidence: 96%